2016
DOI: 10.4254/wjh.v8.i22.924
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol metabolism in cholestatic liver disease and liver transplantation: From molecular mechanisms to clinical implications

Abstract: The aim of this review is to enlighten the critical roles that the liver plays in cholesterol metabolism. Liver transplantation can serve as gene therapy or a source of gene transmission in certain conditions that affect cholesterol metabolism, such as low-density-lipoprotein (LDL) receptor gene mutations that are associated with familial hypercholesterolemia. On the other hand, cholestatic liver disease often alters cholesterol metabolism. Cholestasis can lead to formation of lipoprotein X (Lp-X), which is fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 69 publications
(136 reference statements)
1
42
0
5
Order By: Relevance
“…It is well established that dietary fats and those from de novo lipogenesis in the liver are the two main sources for circulating total cholesterol and triglycerides, which are carried in circulation as VLDL. Elevated circulating total cholesterol and triglycerides may be attributed to increased lipid synthesis, or decreased lipid clearance, or both in the liver [13][14][15][16][17]. In this study, no difference was found in food intake between vehicle-treated mice and olanzapine-treated mice (data not shown).…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…It is well established that dietary fats and those from de novo lipogenesis in the liver are the two main sources for circulating total cholesterol and triglycerides, which are carried in circulation as VLDL. Elevated circulating total cholesterol and triglycerides may be attributed to increased lipid synthesis, or decreased lipid clearance, or both in the liver [13][14][15][16][17]. In this study, no difference was found in food intake between vehicle-treated mice and olanzapine-treated mice (data not shown).…”
Section: Discussionmentioning
confidence: 47%
“…5A-C). Olanzapine deregulates hepatic cholesterol and triglyceride metabolism in apoE -/-mice Hepatic cholesterol and triglyceride metabolism are crucial factors for maintaining the homeostasis of the lipid pool [13,14]. Thus, the effects of olanzapine on hepatic de novo lipogenesis, lipoprotein metabolism, triglyceride synthesis, and secretion, as well as fatty acid oxidation were investigated.…”
Section: Olanzapine Deregulates Cholesterol Flux and Aggravates Inflamentioning
confidence: 99%
See 1 more Smart Citation
“…In a series of 36 cases of TEN with DILI, none of the patients with similar bilirubin serum levels survived [8]. Moreover, hypercholesterolemia is usually associated with episodes of cholestasis [10], and this is also common in cholestatic DILI [9,11,12]. In our patient, cholesterol values took a long time to normalize ( Table 1).…”
mentioning
confidence: 58%
“…CoQ 10 , a ubiquinone redox-active lipophilic antioxidant which is synthesized in the phospholipid membrane of the tissues, seems to play a crucial role in antioxidant system in various organs of animals. Among various organs, the liver is the major organ of cholesterol metabolism including biosynthesis, storage, excretion and converting cholesterol to bile acids under normal circumstances [30]. Therefore, it is necessary to explore the effects of CoQ 10 on the expression of antioxidant genes and lipid peroxidation in the liver of high cholesterol diet fed rats.…”
Section: Discussionmentioning
confidence: 99%